Corneal confocal microscopy for the diagnosis of diabetic peripheral neuropathy: A systematic review and meta‐analysis. Issue 1 (27th August 2021) - Gad, Hoda; Petropoulos, Ioannis N; Khan, Adnan; Ponirakis, Georgios; MacDonald, Ross; Alam, Uazman; Malik, Rayaz A
ABSTRACT: Introduction: Corneal confocal microscopy (CCM) is a rapid non‐invasive ophthalmic imaging technique that identifies corneal nerve fiber damage. Small studies suggest that CCM could be used to assess patients with diabetic peripheral neuropathy (DPN). Aim: To undertake a systematic review and meta‐analysis assessing the diagnostic utility of CCM for sub‐clinical DPN (DPN − ) and established DPN (DPN + ). Data sources: Databases (PubMed, Embase, Central, ProQuest) were searched for studies using CCM in patients with diabetes up to April 2020. Study selection: Studies were included if they reported on at least one CCM parameter in patients with diabetes. Data extraction: Corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), corneal nerve fiber length (CNFL), and inferior whorl length (IWL) were compared between patients with diabetes with and without DPN and controls. Meta‐analysis was undertaken using RevMan V.5.3. Data synthesis: Thirty‐eight studies including 4, 000 participants were included in this meta‐analysis. There were significant reductions in CNFD, CNBD, CNFL, and IWL in DPN − vs controls ( P < 0.00001), DPN + vs controls ( P < 0.00001), and DPN + vs DPN − ( P < 0.00001). Conclusion: This systematic review and meta‐analysis shows that CCM detects small nerve fiber loss in subclinical and clinical DPN and concludes that CCM has good diagnostic utility in DPN. Abstract : This meta‐analysis of 4, 000 participants shows that corneal confocal microscopy is a rapid objective ophthalmic technique for the assessment of subclinical and clinical diabetic neuropathy. Forest plot of corneal nerve fiber length (CNFL) in patients with diabetic peripheral neuropathy (DPN+) and without diabetic peripheral neuropathy (DNP−).